Funkcje obligacji - Bursztynowicz, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Here is a coherent juxtaposition of theses concerning the functions of bonds which appeared in achievements of law and economics doctrine. Functions implemented by bonds doubtlessly indicate serious tasks provided by these financial instruments.Firstly, the importance of this security in economy circulation must be presented economy function. Next, it is necessary to indicate, as it is rightly emphasised in the literature, a division of bonds functions into those referring only to issuers or only to bondholders.Indisputable is the fact that the emission of bonds is to bring the additional financial resources to their issuers loan function, which can be used on issuer’s development development function, restructuring of their activities reconstructing function or an economy balance retrieving and further business continuation stability function. From the issuers’ point of view, bonds are perceived as one of the forms of free resources investment investment function.Nonetheless, bonds can be an attractive rotation of goods, as laws incorporated in them may be carried from the actual owner to another subject paying and circulation function. According to this, a certain level of reliability must be provided that issuers’ obligations resulting from bonds will be realised guaranty function.In the present article, special functions of bonds were enlisted as well as common bonds modifications and the basic and side functions of bonds.
Keywords: obligacje; funkcje obligacji; papier wartościowy; emitent; obligatariusz